Studying the Synthesis of Graphene Oxide in Ammonium Carbonate Solution - Khushnudbek Eshchanov; Makhliyo Ibragimova; Bazar Ibadullaev (Nanochemistry Research)
Studies on the synthesis of graphene oxide in ammonium carbonate solution by electrochemical method were conducted. During the synthesis of graphene oxide, a partial reduction of graphene oxide was observed as a result of stirring the solution. The composition of graphene oxide was analyzed using UV- and ATR-FTIR spectroscopy and quantum chemical calculation methods. As a result of the analysis, it was found that the graphene oxide contains hydroxyl, carboxyl, methylene, methyl, and ether groups connecting aromatic rings. Absorption in the 264 nm region, according to the UV spectrum, indicates a partial reduction of graphene oxide. It is important to carry out the synthesis process in a cold solution of ammonium carbonate because when the solution is warm, the hydrolysis of the salt increases. Ammonia and carbon dioxide gases are released in the hydrolysis process. This research work demonstrates a clean separation of graphene oxide in ammonium carbonate solution.